Effect of Successive At-home Bleaching Sessions on the Surface Properties, Biaxial Flexural Strength, and Reliability of CAD-CAM Monolithic Materials - Queiroz, Jfc [UNESP]; Amaro, L. F. [UNESP]; Massucatto, L. O. [UNESP]; Dovigo, L. N. [UNESP]; Adabo, G. L. [UNESP]; Fonseca, R. G. [UNESP] (Operative Dentistry, 2024)
Although at-home bleaching can recover the optical properties of stained CAD-CAM monolithic materials, little is known about its impact on their surface and mechanical properties, especially when successive sessions are performed. This study evaluated the effect of successive at-home bleaching sessions on the microhardness, roughness, topography, biaxial flexural strength (BFS), and reliability of CAD-CAM monolithic materials. Disks from Lava Ultimate (LU), Vita Enamic (VE), and IPS Empress CAD (EMP) were fabricated and submitted to up to three bleaching sessions. At-home bleaching was performed with 10% carbamide peroxide, and each session consisted of one application for 10 hours/day for 14 days. The analyses of the aforementioned parameters were assessed before and after the first, second, and third bleaching sessions, except for BFS, which was evaluated at baseline and after the third session. The Weibull modulus was calculated from the BFS data. The microhardness of the three materials as well as the roughness of LU were not affected by the sessions, whereas the roughness of VE and EMP increased from the second session. All materials displayed topographic changes, which became more pronounced with the increase in the number of sessions. Although bleaching decreased the BFS of the materials, it did not adversely affect their reliability. Successive at-home bleaching sessions with the protocol used in the present study cannot be considered a safe procedure for the materials evaluated.